The e-commerce market in Kazakhstan: analysis of the state and development directions - A. B. Zhanbozova; T. A. Azatbek; S. N. Valieva; I. N. Tuzelbaeva; K. B. Zhumanazarov (Экономика: стратегия и практика, 2021)
Today, the global world is characterized by active development and widespread penetration of information and communication technologies into various spheres of life. This trend has also influenced the ways and formats of doing business: today, e-commerce is already actively developing, which has provided new development prospects for business in the form of savings on transaction costs, the ability to access global markets without the need to be present on the spot, etc.The purpose of the article is to identify barriers to the development of the e-commerce market in the Republic of Kazakhstan and develop proposals for their elimination. The article examines the problems and reasons for the insufficient level of development of e-commerce in Kazakhstan by analyzing the state of the e-commerce market and the main factors that determine the pace of its development. The reasons for low entrepreneurial activity in the investigated market are identified, with the definition of legal, infrastructural and other barriers to development. The research results can be used as a basis for regulating the e-commerce market. In particular, they results can be used to develop and implement programs to stimulate entrepreneurial activity in the e-commerce market and improve its infrastructure.